2019
DOI: 10.1038/s41438-018-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Wide transcriptional investigation unravel novel insights of the on-tree maturation and postharvest ripening of ‘Abate Fetel’ pear fruit

Abstract: To decipher the transcriptomic regulation of the on-tree fruit maturation in pear cv. ‘Abate Fetel’, a RNA-seq transcription analysis identified 8939 genes differentially expressed across four harvesting stages. These genes were grouped into 11 SOTA clusters based on their transcriptional pattern, of which three included genes upregulated while the other four were represented by downregulated genes. Fruit ripening was furthermore investigated after 1 month of postharvest cold storage. The most important variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…1c). This result further demonstrates that the application of an HMG-CoA reductase inhibitor prevents The change of the volatilome in pear fruit during on-or off-tree ripening is already well documented [36][37][38] . In agreement with these studies, the most important volatiles produced by "Blanquilla" fruit during ripening were esters and alcohols, which resulted to be the VOCs detected at higher concentrations in both untreated and ethylenetreated fruit.…”
Section: Ethylene-dependent and -Independent Pathways Are Involved Insupporting
confidence: 64%
See 1 more Smart Citation
“…1c). This result further demonstrates that the application of an HMG-CoA reductase inhibitor prevents The change of the volatilome in pear fruit during on-or off-tree ripening is already well documented [36][37][38] . In agreement with these studies, the most important volatiles produced by "Blanquilla" fruit during ripening were esters and alcohols, which resulted to be the VOCs detected at higher concentrations in both untreated and ethylenetreated fruit.…”
Section: Ethylene-dependent and -Independent Pathways Are Involved Insupporting
confidence: 64%
“…Two micrograms of RNA isolated from each sample (CT, ET, 1-MCP, and LOV, collected after 4 months of cold storage, and after 4 months of cold storage + 5 days of shelf life at 20°C) were transcribed with the SuperScript VILO cDNA Synthesis kit (Invitrogen). RT-qPCR was carried out with the ViiA7 PCR System (ThermoFisher Scientific) according to the thermal profile described elsewhere 36 . The 18 elements used in the candidate gene transcription profiling were retrieved from the set of DEGs detected through the RNA-Seq analysis or from available literature 8,19 .…”
Section: Candidate Gene Rt-qpcrmentioning
confidence: 99%
“…Comparisons were made to recent studies that examined expression of some relatively well-characterized climacteric fruit ripening genes, ACO, ACS, and PG, photosystem genes and others ( Ziosi et al, 2008 ; Busatto et al, 2019 ). In general our results agreed, though direct comparisons are scarce since sampling for gene activity many months into the postharvest period has not been done extensively ( Supplementary File 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Busatto et al subsequently identified candidate genes by comparing the transcriptome of on-tree maturation and postharvest ripening in fruit of cv. ‘Abate Fetel’ [ 22 ]. By comparing fruit RNA-seq data from different storage times, 13 genes were found related to ethylene biosynthesis and signal transduction were identified in Asian pear, along with 2457 transcription factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%